A Study on the Relationship between Domain Specific Self-Efficacy and Self-Regulation in e-Learning Contexts - Gupta, Priyanka; Bamel, Dr. Umesh (Online Learning, 2023)
Self-regulation has been found to be integral to academic learning in traditional classroom environments. Social cognition theory highlights the significant relationships between academic self-efficacy, internet self-efficacy, and work experience in years on self-regulation in the context of traditional classroom learning. However, there is a lacuna in the literature on the significance of these relationships in the context of e-learning. The exponential growth of e-learning and changes in business environment necessitate a study to examine the effect on self-regulation in the context of e-learning. This research is based on a sample of 525 management students from a business school in South Asia. The findings highlight that academic and internet self-efficacy have a positive effect on self-regulation even in an e-learning environment. e-learning here refers to interactive online learning, in a university setting. The findings have significant implications for both theory and practice as they build on the existing literature. We suggest use of training-based interventions for promoting self-regulation which subsequently would facilitate higher e-learning efficacy.